A The Effect of Job Pressure, Task Complexity, and Work Motivation on Employee Performance with Resilience Ability as a Moderator - Maxi Yehuda; Toni Yoyo (LPPM Universitas Buddhi Dharma, 2025)
Indonesia has risen to 34th place globally in performance competitiveness, up from 44th the previous year, highlighting significant potential for improvement. To maintain and enhance this competitiveness, it is essential to focus on the factors influencing performance. Companies in Indonesia must effectively engage with their employees to foster a productive work environment. This study aims to examine the influence of work pressure, task complexity, and work motivation on employee performance, along with the moderating effect of resilience ability. Utilizing the Structural Equation Modeling (SEM) method and Smart PLS software, the research analyzes data from a sample of 215 respondents, determined based on the Hair method. The findings indicate that work pressure has a direct impact on performance, as does task complexity, suggesting that both factors significantly influence employee outcomes. Additionally, resilience ability moderates the relationship between work pressure and performance, meaning that employees with higher resilience can better cope with job pressures, ultimately enhancing their performance. However, the study found that resilience ability does not significantly moderate the relationships between task complexity and performance, nor between work motivation and employee performance. This indicates that while resilience plays a crucial role in handling work pressure, it may not affect the other dimensions as strongly. The implications of these findings suggest that companies should focus on balancing work pressure and reducing unnecessary task complexity. Additionally, enhancing work motivation is vital for improving overall employee performance. By creating a supportive environment that reduces pressure and complexity while fostering motivation, companies can cultivate a more effective and resilient workforce, contributing to the overall enhancement of Indonesia's global competitiveness.